In Vitro: Influence of Zirconium Coatings on Surface Roughness of (Beta-Titanium III and Timolium Titanium) Orthodontic Archwires (Journal of Medical Sciences, 2020)
The main purpose of this study was to investigate the significance of Zr Coatings and its appropriate thickness on surface roughness of the beta-titanium orthodontic archwires (β-Ti III) and timolium titanium archwires (TIM), Layers of Zr were deposited on the orthodontic archwires and compared the surface roughness before and after Zr deposition. The surface roughness was examined before and after Zr deposition, using scanning electron microscopy (SEM) and atomic force microscopy (AFM). Two commercially available orthodontic archwires were used in this research, namely, β-Ti III and TIM orthodontic archwires. The archwires were cut to 25 mm length specimens. In this study, the electron beam physical vapor deposition (EB PVD) technique was implemented to coat four various thicknesses ( 5, 10, 25, and 50 nm) of pure Zr on selected archwires and the results thereof were investigated using AFM, SEM. SEM and AFM analysis tests of Zr-coated archwires showed significant improvement in their surface roughness compared with uncoated archwires. (TIM) Zr-coated archwires showed lower surface roughness than (β-Ti III) Zr-coated archwires. The improvement of coatings Zr with 50 nm thick was more reliable than that of coatings Zr with 5, 10, and 25 nm. It is concluded that the most available commercial product for orthodontic archwires could be improved by the surface deposition of Zr. coating 50 nm thick of Zr on β-Ti III and TIM orthodontic archwires is recommended for even sliding mechanics due to the resulting reduced surface roughness.